MEMBINA KELUARGA SEJAHTERA MELALUI PENERAPAN 8 FUNGSI KELUARGA - Arri Handayani; Padmi Dhyah Yulianti; Sukma Nur Ardini (IKIP PGRI Bojonegoro, 2018)
ABSTRACTProsperous family is the desire for every individual, but many influential factors to achieve the condition. One is how to implement 8 family functions. Many citizens who do not understand and do not even know about the 8 functions of the family itself. This is evidenced by the many problems that people complain about family problems. Whereas if the community can implement these functions, the existence of family problems can be minimized. This condition is known when the devotees conduct the counseling process in the